Antiviral activities of Schizonepeta tenuifolia Briq. against enterovirus 71 in vitro and in vivo - Sin-Guang Chen (Nature Portfolio, 2017)
Abstract No effective drug is currently available for treatment of enterovirus 71 (EV71) infection. Schizonepeta tenuifolia Briq. (ST) has been used as a herbal constituent of traditional Chinese medicine. We studied whether the aqueous extract of Schizonepeta tenuifolia Briq (STE) has antiviral activity. STE inhibited replication of EV71, as evident by its ability to diminish plaque formation and cytopathic effect induced by EV71, and to inhibit the synthesis of viral RNA and protein. Moreover, daily single-dose STE treatment significantly improved the survival of EV71-infected mice, and ameliorated the symptoms. Mechanistically, STE exerts multiple effects on enteroviral infection. Treatment with STE reduced viral attachment and entry; the cleavage of eukaryotic translation initiation factor 4 G (eIF4G) by EV71 protease, 2Apro; virus-induced reactive oxygen species (ROS) formation; and relocation of heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) from the nucleus to the cytoplasm. It was accompanied by a decline in EV71-associated hyperphosphorylation of p38 kinase and EPS15. It is plausible that STE may inhibit ROS-induced p38 kinase activation, and subsequent hnRNP A1 relocation and EPS15-mediated membrane trafficking in infected cells. These findings suggest that STE possesses anti-EV71 activities, and may serve as health food or candidate antiviral drug for protection against EV71.